Disobedience in Medication and Opportunistic Infection as Lead Factors to HIV/AIDS Mortality at Kencong Public Health Center, Jember - Santi, Maya Weka; Deharja, Atma; Rachmawati, Ervina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Acquired Immunodeficiency Syndrome (AIDS) is defined as a set of symptoms due to decreased immunity caused by the Human Immunodeficiency Virus (HIV). One of the sub-district in Jember which has the highest HIV/AIDS mortality is Kencong with the death number was 55.88% by January-July 2019. The purpose of this research was to analyze related factors to HIV/AIDS mortality at Kencong Public Health Center. Data were collected from HIV/AIDS patients’ medical record documents with 51 samples consisting of 17 samples from the case group and 34 samples from the control group. Analysis data conducted by Chi-Square test using a case-control approach. The results showed that there was a correlation between disobedience in medication and HIV/AIDS patients’ mortality, with p=0,000 and risk of death at 15,682 times OR (Odds Ratio). Likewise, there was a correlation between the patients’ opportunistic infection and the HIV/AIDS patients’ mortality, with p=0,004 and risk of death at 5,958 times OR. However, the variables of sex, age and level of education did not have any correlation with HIV/AIDS patients’ mortality. Kencong Public Health Office should encourage HIV/AIDS patients to improve medication adherence so can reduce the chance of opportunistic infections. Abstrak: Acquired Immunodeficiency Syndrome (AIDS) didefinisikan sebagai sekumpulan gejala akibat penurunan kekebalan yang disebabkan oleh Human Immunodeficiency Virus (HIV). Salah satu kecamatan di Kabupaten Jember yang memiliki angka kematian HIV / AIDS tertinggi adalah Kencong dengan angka kematian 55,88% pada Januari-Juli 2019. Tujuan penelitian ini adalah menganalisis faktor-faktor yang berhubungan dengan kematian HIV / AIDS di Puskesmas Kencong. Pengumpulan data dilakukan dari dokumen rekam medis pasien HIV / AIDS dengan 51 sampel yang terdiri dari 17 sampel dari kelompok kasus dan 34 sampel dari kelompok kontrol. Analisis data dilakukan dengan uji Chi-Square dengan menggunakan pendekatan case-control. Hasil penelitian menunjukkan bahwa ada hubungan ketidakpatuhan dalam pengobatan dengan kematian pasien HIV / AIDS, dengan p = 0,000 dan risiko kematian sebesar 15.682 kali OR (Odds Ratio). Demikian juga terdapat hubungan antara infeksi oportunistik pasien dengan kematian pasien HIV / AIDS, dengan p = 0,004 dan risiko kematian sebesar 5,958 kali OR. Namun variabel jenis kelamin, usia dan tingkat pendidikan tidak memiliki korelasi apapun dengan angka kematian penderita HIV / AIDS. Dinas Kesehatan Kencong harus mendorong pasien HIV / AIDS untuk meningkatkan kepatuhan minum obat sehingga dapat mengurangi kemungkinan terjadinya infeksi oportunistik.